Indonesian and Egyptian EFL university students’ difficulties in reading comprehension - Intan Ummul Baiti; Eros Meilina Sofa (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2023)
Comprehension is an important aspect of every reading activity. Through reading comprehension, readers can understand the content or passage of a text. Nevertheless, many students still experience the difficulties in their English reading comprehension. This study aimed to reveal the Indonesian and Egyptian EFL university students’ difficulties in reading comprehension as well as its causative factors. This study involved two EFL students who are majoring in English Education in semester five. This study used a qualitative method with a narrative inquiry design. Semi-structured interview was implied to collect the data. This study helped to develop the theory of Nuttall (2008) and Alderson (2005) about the difficulties in reading comprehension and the causative factors of its difficulties. Thematic analysis by Barkhuizen, Benson, and Chick was used to analyze the data. The result of this study showed that there were several difficulties faced by the Indonesian and Egyptian EFL university students in reading comprehension. They were namely difficulty in understanding word meaning, understanding long sentences, determining the main idea and making the inference. The next finding reported the factors that caused the students’ difficulties were lack of language knowledge, lack of interest, lack of concentration, and the length of the text.